Priority of theoretical preparation for cyclic sports (on the material of examination of sportsmans and trainers) - Bohuslavska, V. (Studies in Sport Humanities, 2017)
The article presents the results of a survey of qualifi ed athletes and trainers for the priority of the use of various means of theoretical training in the process of multi-year sport improvement in cyclic sports. The survey was attended by 146 qualified athletes and 82 trainers from sports such as rowing, swimming, track and fi eld (running and walking), and ski races. The following research methods were used in the work: theoretical analysis and generalization of literary sources, studying of documentary materials, analysis of personal data, methods of mathematical statistics. It has been established that the need to apply such theoretical training materials as collections of scientifi c articles, study aids, monographs, electronic and audio books, lectures, pedagogical testing, Internet search services increases with each subsequent stage of preparation of athletes. In contrast, the signifi cance of the use of posters, drawings, brochures, animations, documentaries and feature fi lms, games and practical events is reduced with increasing athletic athleticism. At the same time, the most eff ective means of theoretical training, the majority of respondents note the use of search services Internet and the latest technical means of training at all stages of training.